PENGARUH PENGEMBANGAN PRODUK TERHADAP VOLUME PENJUALAN PADA PERUSAHAAN KRIPIK “BUDI JAYA” PROBOLINGGO - Farasandya Amalia Hapsari (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2020)
The purpose of this study was to determine the effect of product development on sales volume in the chip company "BUDI JAYA" PROBOLINGGO. In this study using a quantitative approach. The research was conducted at the "BUDI JAYA" PROBOLINGGO chips company located on Jl. Sunan Giri No.48 Probolinggo tries to draw some conclusions that based on the results of the calculation, it is found that the product development that has been carried out by the company has a significant effect on sales volume. This is evidenced after testing using the t test, it turns out that the t test results are 17.40> t table (1.638), then H0 is rejected. Ha is accepted, which means that product development has a significant effect on sales volume. The relationship between product development variables (X) is very influential on sales volume, this is evidenced by r2 = 67.4% of sales volume is influenced by product development variables and the remaining 32.6% is influenced by other things that are not included in the research variables.